THE REPRESENTATION OF MEXICAN CULTURE IN COCO FILM - Nurlaili, Devi; Asanti, Chris; Nasrullah, Nasrullah (Fakultas Ilmu Budaya Universitas Mulawarman, 2022)
The representation of Mexican culture becomes one of the main focuses on visual media since many visual media display the Mexican as something bad. In Hollywood films, the depictions of Mexican are usually different from the Mexican perspective. Mexico is a place where awful things happen in the film. Coco film is a film that genuinely gives Mexico a good name. It has shown the beauty of Mexico through its culture. The purpose of this research is to find the representation of Mexican culture in Coco film. In order to get more thorough understanding, the theory of Cultural Representation by Stuart Hall was employed. In this research, the researcher used qualitative research methodology. The results of the research show that there are eighteen representations of Mexican culture in Coco film. Those representations are paple picado, piñata, luchador, tamales, pan dulce, alebrijes, xolo dog, cumbia, mariachi, huaraches, hacienda, Aztec pyramid, churros, marimba, el grito, the dominant religion, Dia de los Muertos, and spanish language.